Memórias pedagógicas de professores ribeirinhos do Baixo Amazonas - Pessoa, Jony Alason da Silva (Brasil, 2024)
In this work, we highlight the great importance of analyzing the pedagogical practices experienced by riverside teachers who taught/teach classes in the communities of Barreirinha, in the lower Amazon region, considering mainly the process of knowledge construction, the possibilities of self-education and the resignification of contemporary knowledge in the context of professional and technological education. This research focuses on memories in narratives, telling episodes of lives from an ontological point of view, highlighting moments of resilience, self-education, teacher training and pedagogical practice. Starting from the research problem “How can riverside teachers contribute with the experiences acquired during their training and execution of teaching pedagogical practices in riverside schools based on their narratives?” we traced a guiding thread, with the main objective “To understand records of memories of riverside teachers who tell episodes of their lives in an ontological sense, highlighting moments of resilience, self-education, teacher training and pedagogical practice throughout their teaching work in riverside schools in the lower reaches Amazon.” As for the method, the work presented here is of a qualitative nature based on the foundations of Creswell (2014), as it considers propositions of a research method/methodology. As for the type of research, this in turn is based on narrative research with a focus/approach on autobiography. There is always a story involved, which is always changing. “Experience happens narratively. Narrative research is a form of narrative experience” (Clandinin and Connelly, 2011, p.49). The work is divided into three chapters, all aligned with guiding questions parallel to the specific objectives. The first chapter presents the researcher's formative memorial, in the second chapter the proposal/scope of the research that generated the educational product presented in five stages and even though each one has its specificities, they complement each other and in the third chapter the educational product that The proposal is a workshop where teaching narratives were collected. The study sought valuable insights into the experiences, learnings and strategies developed by these educators, providing a deeper understanding of the unique educational context of these riverside communities in the Amazon region. The narratives also signal a reflection on the democratization of education today, as most riverside schools emerge using digital technologies to provide teachers with new pedagogical experiences linked to teaching practices, knowing that in current times digital technologies are not democratized in our state, that is, new policies are necessary. In short, the theme's texture brought great reflections and significant contributions and greatly impacted the construction of the Educational Product proposed here as “Oficina de Memórias Pedagógicas de Professores Ribeirinhos”, whose contribution focused on self-education, using the digital applications WhatsApp and Facebook as a facilitating resource. /Instagram, which can serve as inspiration for teachers in their current pedagogical practices, and for trainers to make use of this product, based on self-education, teacher training, pedagogical practice and resilience of riverside teachers.